Combined forms of education: experience of the department of obstetrics and gynecology - Siusiuka, V. H.; Kyrychenko, M. M.; Deinichenko, O. V.; Onopchenko, S. P.; Serhiienko, M. Yu.; Сюсюка, Володимир Григорович; Кириченко, Михайло Михайлович; Дейніченко, Олена Валеріївна; Онопченко, Світлана Павлівна; Сергієнко, Марина Юріївна (My University, 2024)
The article examines the impact of wartime on medical education and the role of combined forms of education. Experience from the Department of Obstetrics and Gynecology at Zaporizhzhia State Medical and Pharmaceutical University highlights the effectiveness of integrating online learning and simulation technology in wartime conditions, offering innovative solutions to maintain education quality despite challenges.